NUMERICAL ANALYSIS OF INTER-PHASE MASS TRANSFER WITH CHEMICAL REACTION - Gabbiye, Nigus; Tefera, Nurelegne (Zede Journal of Ethiopian Engineers and Architects, 2023)
The numerical analYJ/.! In the present study Simulates mlerphaJe mass transfer with chelmeal noel/on of two Immucible liqUid! by Jlmu/laneOl.uiy IlOlvrng Iht HigbIe PenetratIon model The transport equations art Jollied numerically for eoncentralion and temperature projiiu 01 Ihl' mler.pilcut using fimte volume me/hod (FVII1) for d,fflWon, and convection dIffUSIOn equaluxu wllh and without chemical reacllon The Jlmu/llllOn resulls art validated UJlng expei'tmentaf dala reported In the IileralUre [1} for CydohUtlne - Acl!llc acid - Water system 711e concentration variation along the horizOI1tai dine/Ion I.J smaller compared to vertical direction Keywords Inler phase ma.u transfer, mfUJ IT(JfUfer .... ,Ilh chemIcal reactIon, man tn:uufer without chemIcal reactlon.fimte volume method